Bagaimana tingkat kepuasan lansia dalam pelayanan kesehatan prolanis di Yogyakarta? - Listyaningsih, Enik; Sinaga, Mei Rianita Elfrida (Jurnal Kesehatan, 2024)
The most common non-communicable diseases in the elderly in Yogyakarta are hypertension and diabetes mellitus. Prolanis is a program that focuses on providing services for hypertension and diabetes mellitus in the elderly. The transition from pandemic to endemic has made prolanis ' service system change which was initially carried out offline to switch to online and back to offline so that it affects the satisfaction of health services felt by the elderly. The number of elderly visits decreased by 30% from the initial observation results. This purpose of this study was to determine the satisfaction of the elderly to health services prolanis. Research methods using quantitative descriptive. Sampling technique used accidental sampling as many as 34 elderly who are prolanis patients who have been registered. Data collection using the satisfaction level questionnaire conducted validity test by researchers with 17 items valid statement with cronbachs's alpha value of 0.861. This study has received ethics from KEPK STIKES Bethesda Yakkum with No. 024 / KEPK.02.01 / III / 2023. Data analysis using descriptive statistics with the results obtained that the majority of elderly people who use prolanis services aged 60 to 74 years ( 67.6%), female gender (79.4%) with Junior High School Education Level (35.3%), and the level of satisfaction category quite satisfied 52.9%. For further research, researchers are expected to explore how treatment adherence prolanis participants.